Tantangan yang Dihadapi Guru dalam Mengembangkan Kompetensi Profesional pada Pembelajaran IPS Sekolah Dasar - Farda_Nur Ariza; Erni; Muhammad Kaulan Karima; Adhista Rizky Wulandari; Cintia Dewi Cahyati; Ni Kadek Indah Sari; Nurul Faida (Jurnal Sociohumaniora Kodepena (JSK), 2025)
This study aims to identify the challenges faced by teachers in developing professional competencies in Social Studies (IPS) instruction at the primary school level. The research background is grounded in the critical role of teachers as facilitators in shaping students’ character, knowledge, and skills through IPS, alongside the various internal and external obstacles that impede efforts to enhance teacher professionalism. A qualitative case-study approach was employed, involving three upper–grade teachers (grades 4–6) at SD Negeri 06 Metro Barat as the main informants. Data were collected via structured interviews and analyzed descriptively. The findings reveal that internal challenges include low teacher motivation—often because teaching is not their primary career choice—limited creativity in designing instructional media, and insufficient time for professional development. External challenges encompass a high administrative workload, rapid curriculum changes, and the abstract nature of IPS, which demands concrete media (such as globes and maps) to facilitate student understanding. Work-related stress arising from administrative demands that exceed teachers’ capacities was also identified as a significant barrier. As recommendations, this study suggests implementing sustained Continuing Professional Development programs, creating engaging and relevant instructional media, providing structured administrative support from the school (e.g., guided supervision and reduced bureaucratic burdens), and establishing teacher learning communities to share best practices. It is hoped that the implementation of these strategies will enhance primary school Social Studies teachers’ professional competencies and, ultimately, improve the quality of instruction.